An Investigation into the Relationship between Stock Market Fluctuations and Mental Health - Ruf, Ruben (Trinity College Dublin. School of Business. Discipline of Business & Administrative Studies, 2025)
Despite mental health being included in one of the United Nation's Sustainable Development Goals, and a plethora of studies providing evidence of the rising economic impact of mental health disorders globally, little is known about the impact of stock market fluctuations on people's mental health. Using panel data from the UK based Understanding Society dataset from 2010 to 2023, I conduct three longitudinal studies to investigate the link between immigrants' mental health and stock market fluctuations in their home countries, and to examine asymmetry and mental health spillover effects in the relationship between people's mental health and stock market fluctuations in their country of residence. I employ a random effects model, pooled ordinary least squares regression and random effects probit model to investigate the impact of stock market volatility in immigrants' home countries on their subjective mental health and diagnosed clinical depressions. I find that the mental health of immigrants is negatively impacted by stock market volatility in their home countries, with the effect reducing as immigrants disintegrate from their home country (measured by the time since first arrived in the UK) and increasing with the immigrants' age at the time of arrival in the UK. I also find that diagnosed clinical depressions as a measure of objective mental health are not affected. Next, I employ a fixed effects model and pooled ordinary least squares regression to investigate how immigrants' subjective mental health is impacted by stock market returns in their home countries, and the role familiarity (measured by cultural, geographic and economic distance, and whether the same language is spoken in the home country and the UK) plays in this relationship. I find that immigrants' subjective mental health is positively impacted by one-day lagged returns in their home country. I also find that daily stock market returns have an immediate impact on immigrants' subjective mental health if they have income from interest or dividends, or if they are retired. Furthermore, I find that stock market returns have a positive impact on the subjective mental health of immigrants from countries that are developed, and geographically or economically close to the UK, and a negative impact on immigrants from countries that are culturally, geographically and economically distant to the UK, from developing countries, or from countries where English is commonly spoken. Finally, I employ a fixed effects model, pooled ordinary least squares regression and an asymmetric fixed effects model to investigate asymmetry and spillover effects in the relationship between people's subjective mental health and stock market fluctuations in their country of residence. I find that 52-week returns have a symmetric positive impact on subjective mental health, while 52-week volatility has a symmetric negative impact on subjective mental health. I also find that a decreasing stock market index has a stronger impact on subjective mental health than an increasing one. Lastly, I provide evidence that the mental health impairment due to negative 52-week returns spills over to affect investors' household members.
APPROVED
Keywords: clinical depression; mental health; immigration; asymmetric fixed effects; prospect theory; spillover effects; stock market performance; stock market volatility; well-being